Effect of hydrocortisone on interleukin-6 production in human ,peripheral blood rnononuclear ceils - Y. Hirooka; T. Mitsuma; T. Nogimori; Y. Ishizukis (Mediators of Inflammation)
The effect of hydrocortisone on the production of interleukin-6 (IL-6) in human peripheral blood mononuclear cells was studied. Using our newly developed radioimmunoassay system for IL-6 of which specificity, reproducibility, sensitivity and usefulness have been demonstrated. IL-6 production in peripheral blood mononuclear cells of ten normal subjects revealed that in lipopolysaccharide (LPS, 10μg/ml)-stimulation, the mean ± SD of IL-6 was 2.71 ± 0.85 ng/ml. No detectable amount of IL-6 was observed in the absence of LPS and in the presence of hydrocortisone alone. Hydrocortisone (10−10 M to 10−3 M) inhibited LPS-stimulated IL-6 production in a dose-dependent manner. However, there was a wide variation in the response to hydrocortisone, namely, ranging from steroid-sensitive to steroid-resistant. Based on the concentration required to inhibit 50% of LPS-stimulated IL-6 production, three of ten subjects were at 10−6 M, three at 10−5 M and the rest at 10−4 M, respectively. The dramatic anti-inflammatory and immunosuppressive effects of glucocorticosteroids can be life-saving in autoimmune diseases. The present findings suggested that there existed the differences in susceptibility to glucocorticosteroids even among normal subjects, providing some implications for the drug treatment, and also gave further evidence that there may exist an immunoregulatory feedback circuit between the immune and neuroendocrine systems.